-
Notifications
You must be signed in to change notification settings - Fork 2
/
Copy path06.tex
350 lines (306 loc) · 12.7 KB
/
06.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
\section{Lecture -- Week 6}
If $t\colon A\to B$ is a surjective map, then
$a\sim a_1\Longleftrightarrow t(a)=t(a_1)$
defines an equivalence relation on $A$. The set $\overline{A}$
of equivalence classes is in bijective correspondence with $B$,
$\overline{A}\to B$, $\overline{a}\mapsto t(a)$.
Moreover, if $|t^{-1}(\{b\})|=m$ for all $b\in B$, then
$|A|=m|\overline{A}|=m|B|$.
\begin{proposition}
Let $E/K$ be algebraic and $F/K$ be a subextension such that
$E/F$ is finite. Then $\gamma(E/K)=\gamma(E/F)\gamma(F/K)$.
\end{proposition}
\begin{proof}
Assume first that $E=F(x)$.
Let $C$ be an algebraic closure of $K$ containing $E$
and $G=\Gal(C/F)$. Let $f=f(x,F)=\sum b_iX^i$.
The map
\[
\lambda\colon \Hom(E/K,C/K)\to\Hom(F/K,C/K),\quad
\sigma\mapsto\sigma|_F,
\]
is well-defined.
%It is an exercise to check that the map
It is surjective:
if $\varphi\in\Hom(F/K,C/K)$, then $\varphi\colon F\to C$ is,
in particular, a field homomorphism. Since $E/F$ is algebraic, by Proposition \ref{pro:Artin}
there exists a field homomorphism
$\sigma\colon E\to C$ such that $\sigma|_F=\varphi$. Since $\sigma|_K=\varphi|_K=\id$, in particular
$\sigma\in\Hom(E/K,C/K)$.
For $\varphi\in\Hom(F/K,C/K)$,
\[
\lambda^{-1}(\{\varphi\})=\{\sigma\in\Hom(E/K,C/K):\sigma|_F=\varphi\}
\]
and let $R_\varphi$ be the set of roots (in $C$) of the polynomial $\overline{\varphi}(f)=\sum\varphi(b_i)X^i$.
\begin{claim}
The map $\alpha\colon \lambda^{-1}(\{\varphi\})\to R_{\varphi}$, $\sigma\mapsto\sigma(x)$, is well-defined.
\end{claim}
We need to show that $\sigma(x)$ is a root of $\overline{\varphi}(f)$:
\begin{align*}
\overline{\varphi}(f)(\sigma(x))&=\sum \varphi(b_i)\sigma(x)^i
=\sum\sigma(b_i)\sigma(x^i)\\
&=\sum\sigma(b_ix^i)=\sigma\left(\sum b_ix^i\right)=\sigma(f(x))=\sigma(0)=0.
\end{align*}
\begin{claim}
The map $\beta\colon R_{\varphi}\to \lambda^{-1}(\{\varphi\})$, $y\mapsto\sigma_y$,
where $\sigma_y(z)=\overline{\varphi}(h)(y)$
if $z=h(x)$, is well-defined.
\end{claim}
We need to show that if $z=h(x)$ and
$z=h_1(x)$ for some $h,h_1\in F[X]$, then
\[
\overline{\varphi}(h)(y)=\overline{\varphi}(h_1)(y).
\]
The assumptions imply that
$(h-h_1)(x)=0$ and hence $f$ divides $h-h_1$. Since
$\overline{\varphi}$ is a ring homomorphism,
$\overline{\varphi}(f)$ divides $\overline{\varphi}(h)-\overline{\varphi}(h_1)$.
This implies $(\overline{\varphi}(h)-\overline{\varphi}(h_1))(y)=0$. We also need to show that
$\sigma_y|_F=\varphi$: if $a\in F$, then
write $a=aX^0\in F[X]$. Thus
$\sigma_y(a)=\overline{\varphi}(aX^0)(y)=\varphi(a)\in C$.
It is now an exercise to prove that $\sigma_y\in\Hom(E/K,C/K)$.
\begin{claim}
$|\lambda^{-1}(\{\varphi\})|=|R_\varphi|$.
\end{claim}
For this we need to show that $\beta$ is
the inverse of $\alpha$, that is
$\alpha\circ\beta=\id$ and $\beta\circ\alpha=\id$.
To prove that $\beta\circ\alpha=\id$
let $\sigma$ be such that $\sigma|_F=\varphi$.
Then $y=\sigma(x)\in R_\varphi$. Let
\[
z=h(x)=\sum a_ix^i\in F[x]=E.
\]
Then
\[
\overline{\varphi}(h)(y)=\sum\varphi(a_i)y^i=\sum\sigma(a_i)y^i
=\sigma\left(\sum a_ix^i\right)=\sigma(z).
\]
Conversely, if $y\in R_\varphi$, then
\[
\alpha(\sigma_y)=\sigma_y(x)=y,
\]
as $\sigma_y(x)=\overline{\varphi}(X)(y)=y$.
\begin{claim}
If $\phi\in\Gal(C/K)$ is such that $\phi|_F=\varphi$, then
$|\phi^{-1}(R_\varphi)|=|R_{\varphi}|$ and
\[
O_{G}(x)=\phi^{-1}(R_\varphi).
\]
\end{claim}
Let us first prove $O_{G}(x)\supseteq \phi^{-1}(R_\varphi)$.
If $y\in R_{\varphi}$,
then
\begin{align*}
f(\phi^{-1}(y))&=\sum b_i\phi^{-1}(y^i)=\phi^{-1}\left(\sum\phi(b_i)y^i\right)\\
&=\phi^{-1}(\overline{\varphi}(f)(y))=\phi^{-1}(0)=0.
\end{align*}
Then $f(x,F)=f(\phi^{-1}(y),F)$. By Proposition \ref{pro:conjugate}, $\phi^{-1}(y)\in O_G(x)$.
Now we prove $O_{G}(x)\subseteq\phi^{-1}(R_\varphi)$.
Let $z\in O_{G}(x)$. Then $\overline{\varphi}(f)(\phi(z))=0$, as
\begin{align*}
\overline{\varphi}(f)(\phi(z))&=\sum\varphi(b_i)\phi(z^i)\\
&=\sum\phi(b_i)\phi(z^i)
=\phi\left(\sum b_iz^i\right)
=\phi(f(z))=\phi(0)=0.
\end{align*}
\medskip
Thus $\phi(z)\in R_{\varphi}$ and hence $z\in\phi^{-1}(R_{\varphi})$.
It follows that $|\lambda^{-1}(\{\varphi\})|=|O_{G}(x)|$ for
all $\varphi$. By using the argument
before the proposition,
\begin{align*}
\gamma(E/K)&=|\Hom(E/K,C/K)|\\
&=|O_{G}(x)||\Hom(F/K,C/K)|\\
&=|O_{G}(x)|\gamma(F/K).
\end{align*}
Since $\gamma(E/F)=\gamma(F(x)/F)=|O_{G}(x)|$ by Proposition \ref{pro:gamma_orbit}, the claim follows.
\medskip
For the general case, we assume that $E=F(x_1,\dots,x_n)$. We proceed
by induction on $n$. If $n=0$, then $E=F$ and the result is trivial.
If $n>0$, let $L=F[x_1,\dots,x_{n-1}]$ and $E=L(x_n)$. The
case proved
implies that $\gamma(E/F)=\gamma(E/L)\gamma(L/F)$. By the inductive
hypothesis, $\gamma(L/K)=\gamma(L/F)\gamma(F/K)$. Thus
\[
\gamma(E/F)\gamma(F/K)=\gamma(E/L)\gamma(L/F)\gamma(F/K)
=\gamma(E/L)\gamma(L/K)=\gamma(E/K),
\]
again using the previous case.
\end{proof}
\subsection{Separable extensions}
\begin{definition}
\index{Extension!separable}
\index{Element!separable}
Let $E/K$ be an extension and $x\in E$ an algebraic element over $K$. Then
$x$ is \emph{separable} over $K$ if $x$ is a simple root
of $f(x,K)$.
\end{definition}
An algebraic extension $E/K$ is \emph{separable}
if every $x\in E$ is separable over $K$. Then $K/K$ is separable.
\begin{exercise}
Prove that
an element $x$ is separable over $K$ if and only if $x$ is a simple root
of a polynomial with coefficients in $K$.
\end{exercise}
If $F/K$ is a subextension of $E/K$ and $x\in E$ is separable over $K$, then
$x$ is separable over $F$.
\begin{exercise}
If $C$ is an algebraic closure of $K$, $x\in C$ and $G=\Gal(C/K)$.
Prove that the following statements are equivalent:
\begin{enumerate}
\item $x$ is separable over $K$.
\item Every $y\in O_G(x)$ is separable over $K$.
\item $\gamma(K(x)/K)=[K(x):K]=\deg f(x,K)$.
\end{enumerate}
\end{exercise}
Let $K$ be any field and $g\in K[X]$. Let $z$ be a root of $g$.
Then $z$ is a multiple root of $g$ if and only if $z$ is a root of $g'$.
\begin{exercise}
Prove that if $K$ has characteristic zero or $K$ is finite, then
every algebraic extension of $K$ is separable.
\end{exercise}
%Let $K$ be a field and $g\in K[X]$. Let $z$ be a root of $g$. Then %$z$ is a multiple root of $g$ if and only if $z$ is a root of $g’$.
%Assume first that $K$ has characteristic zero. If $x$ is a multiple root of $f(x,K)$, then
%$f(x,K)$ divides $f(x,K)’$, a contradiction (take degree).
%
%Assume now that $K$ has characteristic $p>0$. Let $f=f(x,K)$. If $x$ is a multiple root of $f$, we repeat the previous argument.
%Assume that $f=\sum_{i=0}^n a_iX^i$ and $0=f’=\sum_{i=1}^n a_iiX^{i-1}$. Then $a_i=0$ if $p$ does not divide $i$. Thus
%$f=\sum_{k=0}^r b_kX^{pk}$. If $K$ is finite, the map $\alpha\mapsto\alpha^p$ is an automorphism of $K$. In particular,
%every element of $K$ is a $p$-power. Thus, for every $k$, there exists $c_k\in K$ such that $b_k=c_k^p$. Therefore
%$f=\sum_{k=0}^r c_k^pX^{pk}=\left(\sum_{k=0}^r c_kX^k\right)^p$, a contradiction, as $f$ is irreducible.
%A consequence:
%Let $E/K$ be a finite extension. Then $E/K$ is separable
%if and only if $\gamma(E/K)=[E:K]$.
%Let $x\in E$, Then
%\[
%[E:K]=[E:K(x)][K(x):K]\geq \gamma(E/K(x))\gamma(K(x)/K)=\gamma(E/K).
%\]
%This implies that
%\begin{align*}
% [E:K(x)][K(x):K]=\gamma(E/K(x))\gamma(K(x)/K).
%\end{align*}
%Then $[E:K(x)]=\gamma(E/K(x))$ and $[K(x):K]=\gamma(K(x)/K)$ because
%$[E:K(x)]\geq \gamma(E/K(x))$ and $[K(x):K]\geq \gamma(K(x)/K)$. Therefore
%$x$ is separable over $K$.
%
%Conversely, let $E=K(x_1,\dots,x_n)$. We proceed by induction on $n$. The case $n=0$ is trivial, as $E=K$. If $n>0$,
%let $F=K(x_1,\dots,x_{n-1})$ and $E=F(x_n)$. Note that $x_n$ is separable over $K$, so $x_n$ is separable over $F$. Thus
%\[
%[E:K]=[E:F][F:K]=\gamma(E/F)\gamma(F/K)=\gamma(E/K).
%\]
%
\begin{example}
Let $E=\Q(\sqrt{2},\sqrt{3})$. Then
$[E:\Q]=4$ and
$\Gal(E/Q)\simeq C_2\times C_2$. The extension $E/Q$ is normal,
as it is the decomposition field of $(X^2-2)(X^2-3)$ and
it is separable as $\Q$ has characteristic zero.
% If $\sigma\in\Gal(E/\Q)$, then
% $\sigma(\sqrt{2})\in\{-\sqrt{2},\sqrt{2}\}$ and
% $\sigma(\sqrt{3})\in\{-\sqrt{3},\sqrt{3}\}$.
\end{example}
% Q<x> := PolynomialRing(Rationals());
% E := SplittingField((x^2-2)*(x^2-3));
% Degree(E);
% GroupName(GaloisGroup(E));
\begin{example}
Let $E$ be a decomposition field of $X^4-2$ over $\Q$.
Then $E/\Q$ is normal and separable. Note that
$E=\Q(\sqrt[4]{2},i)$, so
\[
[E:\Q]=8=|\Gal(E/\Q)|.
\]
Let us compute
$\Gal(E/\Q)$. If $\sigma\in\Gal(E/\Q)$, then
$\sigma(\sqrt[4]{2})\in\{\sqrt[4]{2},-\sqrt[4]{2},\sqrt[4]{2}i,-\sqrt[4]{2}i\}$ and
$\sigma(i)\in\{-i,i\}$. Two examples are
\[
\alpha\colon\begin{cases}
\sqrt[4]{2}\mapsto\sqrt[4]{2}i,\\
i\mapsto i,
\end{cases}
\quad
\beta\colon\begin{cases}
\sqrt[4]{2}\mapsto\sqrt[4]{2},\\
i\mapsto -i.
\end{cases}
\]
It follows that
$\Gal(E/\Q)$ is isomorphic to the group $\langle\alpha,\beta\rangle$, which turns out to be
isomorphic to the dihedral group
of eight elements.
\end{example}
% Q<x> := PolynomialRing(Rationals());
% E := SplittingField(x^4-2);
% Degree(E);
% GroupName(GaloisGroup(E));
Another consequence: If $E=K(S)$, then $E/K$ is separable if and only if
every $x\in S$ is separable over $K$. One first does the case $E=K(x)$
and then proceeds by induction.
\begin{exercise}
\label{xca:separable1}
Let $K\subseteq F\subseteq E$ be a tower of fields. Prove that
$E/K$ is separable if and only if $F/K$ and $E/F$ are separable.
\end{exercise}
%If $E/K$ is separable, then $F/K$ and $E/F$ are separable (easy). Conversely, assume that $F/K$ and $E/F$ are separable. Let $x\in E$ and
%$f=f(x,K)$. Then $x$ is a simple root of $f$. Let $L=K(S)$, where $S$ is the set of coefficients of $f$. Then $L\subseteq F$, $L/K$ is finite and separable and $x$ is separable over $L$. Thus
%\[
%[L(x):K]=[L(x):L][L:K]=\gamma(L(x)/L)\gamma(L/K)=\gamma(L(x)/K).
%\]
%Hence $L(x)/K$ is separable, and $x$ is separable over $K$.
\begin{exercise}
\label{xca:separable2}
Let $E/K$ and $F/K$ be extensions. Prove that if $F/K$ is separable,
then $EF/E$ is separable.
\end{exercise}
% This follows because $EF/E$ is algebraic and
% $EF/E=E(F)/E$ is generated by separable elements.
\index{Extension!separable}
\label{separable}
If $E/K$ is algebraic, then
\[
F=\{x\in E:x\text{ is separable over }K\}
\]
is a subfield of $E$ that contains $K$. It is known as
the \emph{separable closure} of $K$ with respect to $E$.
Note that $F=K(F)$, as
$K(F)$ is separable because it is generated by separable elements. Moreover,
$F/K$ is separable and
$E/F$ is a \emph{purely inseparable} extension, meaning that
for every $x\in E\setminus F$, the polynomial $f(x,F)$ is not separable.
\begin{proposition}
\label{pro:monogenic}
If $E/K$ is separable and finite, then $E=K(x)$ for some $x\in E$.
\end{proposition}
\begin{proof}
Let us assume that $K$ is finite. Then $E$ is finite and hence
the multiplicative group $E^{\times}=E\setminus\{0\}$
is cyclic, say $E^{\times}=\langle x\rangle$. It follows
that $E=K(x)$.
Let us now assume that $K$ is infinite. We first consider the case
$E=K(x,y)$. The general case $E=K(x_1,\dots,x_n)$ is left as an exercise, one needs to proceed by induction.
Let $n=[E:K]$ and
$C$ be an algebraic closure of $K$ containing $E$.
Write $\Hom(E/K,C/K)=\{\sigma_1,\dots,\sigma_n\}$. Let
\[
f=\prod_{1\leq i<j\leq n}\left((\sigma_i(y)-\sigma_j(y))
+X(\sigma_i(x)-\sigma_j(x))\right)\in C[X].
\]
Then $f\ne 0$, as $f$ is a product of non-zero polynomials. Since $K$ is infinite,
there exists a non-zero
$c\in K$ such that $f(c)\ne 0$. For any $r,s\in\{1,\dots,n\}$ with
$r\ne s$,
\[
\sigma_r(y)-\sigma_s(y)+c(\sigma_r(x)-\sigma_s(x))\ne 0,
\]
as $f(c)\ne0$. It follows that $\sigma_r(y+cx)\ne\sigma_s(y+cx)$. Thus $\gamma(K(y+cx)/K)\geq n$.
Now
\[
n\geq [K(y+cx):K]=\gamma(K(y+cx)/K)\geq n,
\]
so $[K(y+cx):K]=n$ and
hence $K(y+cx)=E$.
\end{proof}
For example, $\Q(\sqrt{2},i)=\Q(\sqrt{2}+i)$.